Legal Perspectives on the Intersections of Religion, Race and Gender – Problems and Solutions - Fehr, Stephie (Richtmann Publishing, 2012)
The paper analyses the intersections of religion, race and gender from a legal perspective. Existing legal scholarship in thisarea has provided a number of accounts, reporting mainly from European jurisdictions, as well as from the jurisprudence of theEuropean Court of Human Rights. The aim of this paper is to first explain how law has contributed to the exclusion of individuals linked toa specific religion, race and gender. Examples of religious discrimination claims highlight particular detriment experienced mostly, but notexclusively, by religious and ethnic minority women in the majority of jurisdictions. These instances reflect that religion is more often thannot the main or sole focal point in court or legislation, whereas the deliberate or accidental effect on women and/or ethnic minorities isconveniently ignored. In its second part, the paper will then move on to elaborating potential solutions for such undesirable outcomes oflaw. The available legal solutions entail various advantages and disadvantages, however, a model of ‘reasonable accommodation’ willbe proposed as the preferable answer at this point in time. Nevertheless, the paper also provides reasons for complementing legalsolutions with non-enforceable measures, such as the facilitation of interfaith dialogue and the raising of awareness of equality anddiversity.